2018
DOI: 10.1021/acs.biochem.8b01013
|View full text |Cite
|
Sign up to set email alerts
|

The Folding and Aggregation Energy Landscapes of Tethered RRM Domains of Human TDP-43 Are Coupled via a Metastable Molten Globule-like Oligomer

Abstract: Stress-induced misfolding and intraneuronal aggregation of the highly conserved nucleic acid binding protein TDP-43 (transactive response DNA binding protein 43 kDa) and its fragments have been implicated in amyotrophic lateral sclerosis and several other neurodegenerative diseases. However, the physicochemical mechanism of its misfolding from the functional folded state is poorly understood. TDP-43 is a four-domain protein and performs the essential nucleic acid binding function with the help of its two tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(80 citation statements)
references
References 65 publications
3
77
0
Order By: Relevance
“…The expression and the purification protocol of TDP-43 tRRM (UniProtKB/ Swiss-Prot entry Q13148) have been described previously. 34 The pure protein was stored in a buffer containing 10 mM potassium phosphate, 150 mM KCl, and 1 mM dithiothreitol (DTT) (pH 7.2). Sodium dodecyl sulfate−polyacrylamide gel electrophoresis revealed that the protein was highly pure.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression and the purification protocol of TDP-43 tRRM (UniProtKB/ Swiss-Prot entry Q13148) have been described previously. 34 The pure protein was stored in a buffer containing 10 mM potassium phosphate, 150 mM KCl, and 1 mM dithiothreitol (DTT) (pH 7.2). Sodium dodecyl sulfate−polyacrylamide gel electrophoresis revealed that the protein was highly pure.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The buffers used at different pH values have been reported previously. 34 A molar extinction coefficient of 15470 M −1 cm −1 at 280 nm was used to determine the protein concentration.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NTD is folded [38][39][40][41] and essential to fulfill native functional processes and necessary for pathological aggregation [36,[42][43][44]. RRM1 and RRM2 domains are also folded and bind UG-rich segments of RNA [45][46][47], and it has been proposed that RRM2 may contribute to the pathological misfolding [48,49]. The pathological form of TDP-43 in ALS and FTLD is hyperphosphorylated, ubiquitinated, and proteolytically cleaved into C-terminal fragments (CTFs) [16,50].…”
Section: Introductionmentioning
confidence: 99%